A multi‐frequency high‐gain GNSS array antenna for asteroid sampling return. Issue 14 (7th October 2022) - Liu, Zhijia; Lu, Fan; Duan, Jiangnian; Huang, Yuhan; Sun, Dayuan; Sun, Yinlong
Abstract: An almost all‐metal L band multi‐frequency high‐gain GNSS array antenna for an asteroid sampling return mission has been developed for orbit determination. The proposed antenna is designed for reception and is compatible with Beidou and GPS at L‐band (i.e. GPS‐L1: 1575.42 MHz; BDS‐B1I: 1561.098 MHz; BDS‐B2a: 1176.45 MHz). The radiation element is an almost all‐metal dipole with structure improvement, and thereby strong enough to handle vibrations and loads. The array antenna is composed of the 7‐radiation element and a low loss air suspended stripline beam‐forming network. The six elements around the center element have uniform distribution, while the center one is excited twice amplitude than outer ones for appropriate gain and beamwidth. A prototype of the proposed GNSS array antenna is designed in a simulation and measured in an experiment. The simulated and measured results agree very well, showing that the reflection coefficient <−17.5 dB over 32.8% bandwidth from 1.1 to 1.7 GHz is achieved with rotationally symmetric radiation patterns and gains >13.4 dBic, 15.2 dBic, 15.2 dBic at BDS‐B2a, GPS‐L1, BDS‐B1I, respectively.